Polypoid endometriosis mimicking invasive cancer in an obese, postmenopausal tamoxifen user - William T. Jaegle; Jason C. Barnett; Bridget R. Stralka; Nicole P. Chappell (Elsevier, 2017)
Background: Tamoxifen is a medication often used for the treatment and prevention of breast cancer. It is classically associated with several gynecological side effects to include a thickened endometrial stripe, increased uterine polyp formation, and an increased risk of uterine cancer. Rarely tamoxifen use has been associated with proliferation of endometriosis often severe enough to mimic a late-stage gynecologic malignancy. Case: A 62-year-old Gravida 0 postmenopausal female with a medical history of severe obesity, infertility, and preventative tamoxifen use presented for evaluation of gross hematuria. A CT urogram was performed and demonstrated findings concerning for carcinomatosis, likely gynecologic in origin. Cervical cancer screening was up-to-date and she had a negative colonoscopy within the prior 2 years. Serum tumor markers were remarkable only for a mildly elevated CA125 of 37.6. Diagnostic laparoscopy demonstrated apparent operable carcinomatosis limited to the pelvis. The procedure was converted to an exploratory laparotomy, where radical tumor cytoreduction was performed to no gross residual disease. Frozen sections performed intraoperatively were unclear of origin but suggestive of low malignant potential. Final pathology resulted for endometriosis. Conclusion: This case illustrates a presentation of endometriosis in a postmenopausal woman mimicking advanced mullerian malignancy. The patient's estrogenic state from obesity in combination with the agonist action of the tamoxifen likely contributed to her rare presentation. While findings such as a thickened endometrial stripe are typical of tamoxifen use, such widespread proliferation of endometriosis resulting in a pelvic mass, genito-urinary obstruction, and plaque-like pelvic spread are not. Précis: Endometriosis is a benign estrogen dependent condition rarely problematic in a postmenopausal patient. Tamoxifen use in the setting of an obese patient may contribute to a proliferation of pre-existing endometriosis which resembles an aggressive late-stage gynecological malignancy.